The Relationship Between LRP-5 and LRP-6 Gene Mutations and Postmenopausal Type 2 Diabetes and Obesity - Jun Li; Ya Li; Yunqiu Lu; Siyuan Li; Yecheng Zhu; Chuanbing Sun; Partab Rai; Xuehai Jia (Clinical Medicine Insights: Endocrinology and Diabetes)
Background: Single nucleotide polymorphisms (SNPs) in the low-density lipoprotein receptor-related protein 5 (LRP5) and the low-density lipoprotein receptor-related protein 5 (LRP6) genes have been implicated in the pathogenesis of type 2 diabetes mellitus (T2DM) and obesity (OB). This study aimed to evaluate the polymorphisms in LRP5 and LRP6 genes in postmenopausal patients with T2DM and OB. Methods: Participants were categorized into the Non-T2DM group (n = 53) and the T2DM group (n = 89) based on glycemic levels. Baseline data and biochemical indices were collected, Bone mineral density (BMD) was measured using dual-energy X-ray absorptiometry, and SNPs at the LRP5 and LRP6 loci were assessed by time-of-flight mass spectrometry. Results: 1. There was a statistical difference in the distribution of genotypes (CC/CT) at locus rs4988331 (χ2 = 67.940, P  = .000) and in the distribution of alleles (C/T) between the T2DM and non-T2DM groups (χ2 = 50.506, P  = .000). Additionally, there were significant differences in the allele (G/A) at locus rs11054704, and both allele (G/T) and genotype (GG/GT) distributions at locus rs1181334 between the OB group and the normal weight group ( P  < .05). 2. OB was identified as a risk factor for T2DM in individuals with the wild-type at locus rs1181334, and the interaction between wild-type and mutant was significant ( P  < .05). 3. Multifactorial logistic regression analysis revealed that BMD (OR 3.755; 95% CI, 1.215-11.608) and triglyceride-glucose (TyG) index (OR 2.855; 95% CI, 1.361-5.986) were risk factors for T2DM in postmenopausal women, whereas alkaline phosphatase (ALP; OR 0.970; 95% CI, 0.945-0.995) and rs4988331 mutation (OR 0.018; 95% CI, 0.006-0.060) were protective factors. Conclusion: Mutations at the LRP5-rs4988331 locus, as well as the LRP6-rs11054704 and rs1181334 loci, may be associated with the development of T2DM and OB in postmenopausal women.